The relevance of critical pedagogy to women in further and higher education and to transitioning lecturers. Issue 1 (2nd January 2019) - Hedges, Cheryl; Kadi-Hanifi, Dr. Karima
ABSTRACT: This paper seeks to reflect upon the critical pedagogy of two university lecturers and authors of this article. It details their experiences of transition reflecting and mirroring those of working class women learners in Further and Higher Education. One voice is that of a lecturer transgressing class boundaries. Fears for her include ' starting over', ' what is an academic', ' fitting in', as well as dissonance due to her gender and class identity. At university, 'uncertainty and danger' allow for identification with students. The other lecturer's narrative is that of transition between two universities. This experience creates uncertainty in action and praxis, thus dissonance too. Fears include ' lack of agency', powerful experiences and views that cannot be transported easily to a new context, ' transformation being halted', ' being in limbo' . Finally, we relate the story of the educational experience of working class women. These women are unable to navigate the neoliberal market as they are constrained by complex responsibilities. Educational transformation is obvious, but many are inhibited by the need to prove the degree`s worth in the "outside world". We consider and challenge the neoliberal discourse framed by the language of "student voice" – a shallow consumer model, undermining genuine democratic dialogue. This voice speaks to the illusion of choice and freedom. These three situations of women returners, as a group of students and two lecturers, or of women transitioning or transgressing, are distinguished by the learning and teaching dissonant emotion of changing (or transforming) oneself and others, whilst still remaining agentic. Indeed, dissonance can affect all three contexts, differently, but powerfully nonetheless. We ask: How can we as educators maintain integrity in the foreign land that is 'neo-liberalism'? How we might share real life stories among pedagogues to challenge the neoliberal framework, the commodification of education and the disempowerment of learners and educators?